The New Face of Slavery in the Balkans - Isilda Mara (The Vienna Institute for International Economic Studies (wiiw), 2009)
The paper studies the individuals from the Balkans, who attempted to migrate illegally and fell victims of trafficking and exploitation at the destination country. The paper aims to analyse and explore the relationship between personal characteristics, previous economic status of the victims and the implications of being trafficked and sexually exploited, in wellbeing terms. In order to examine the deprivation of the victims of trafficking and exploitation we use Sens capability approach whereas to estimate the latent state of well-being we make use of MIMIC approach (Multiple Indicators Multiple Causes). The probability of being trafficked and exploited out of the region and its main determinants are analysed by counting for demographic, social, economic and political factors. We find that improving the political and economic situation in the origin country, concurrently with law enforcement intervention in the destination country, reduces the victims` deprivation by the trafficking and exploitation.
Keywords: 330; human trafficking; illegal migration; capability approach; well-being